THE IMPACT OF SAUDIS’ ATTITUDES TOWARDS GRAFFITI - Mansour Dhafer Al Qarni; Abdullah Hassan Al Qarni, (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
Inscription is a common and a widely used literary technique in communication. This technique is used to deliver an underlying message indirectly. The intended meaning of the words used in inscription form is different from its actual meaning. This literary device is used actively in the Western World and there have been many studies on this area conducted by several researchers. Though inscription on the restrooms is also used by citizens of Saudi Arabia in their communication. Thus, toilet graffiti is a unique window into the relationship between gender, language, and social context. Whereas, the other public places have less painting, drawing and relationship between both genders. Therefore, we would like to propose this paper in Saudi’s graffiti. Also, the importance of how women and men communicate, no comparable situation in which both men and women write graffiti has ever been studied. This study sought to set a new benchmark: focusing not only on at the topic of graffiti but also at the language style in which inscriptions were written, and not in male and female toilets but also in an analogous mixed-gender context in different places. Strong gender differences are found for topic in the findings. Female’s Graffiti tends to be politer, love, relationship, less assertive and interactive, whereas those from the male graffiti indicate more argumentative and negative behavior with racial discrimination. One of the most important results is indicated that both genders are used graffiti in toilet stall in order to express their attitude, psychological case whether positively or negatively. They want to keep on themselves away from their people sights. Gender differences in language style are subtler but generally consistent with those found in other contexts. Gendered language is mitigated in the mixed-gender context. Topics in the mixed-gender context are a composite of the topics found in the men’s and women graffiti but also included the only sexist remarks in the data.